2020
DOI: 10.1155/2020/8724546
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microecological Preparations on Obese Patients after Bariatric Surgery: A Systematic Review and Meta‐Analysis

Abstract: Vitamin deficiency, bacterial overgrowth, and gastrointestinal symptoms can be detected in obese patients after bariatric surgery that influences their quality of life (QoL) and weight. It is unclear if microecological preparations benefit obese patients following bariatric surgery. The aim of this study is to investigate the effects of microecological preparations on QoL, excess weight loss (EWL), and levels of vitamin B12 and inflammatory markers. We searched seven databases to identify reports published til… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In addition, in some studies, the effect of consuming prebiotics, probiotics, and synbiotics was not reported separately, and their collective impact was stated in comparison with the control group. BMI ( 56 , 110 ) and weight reduction ( 56 , 111 ) were observed in some studies, but a neutral effect on BMI ( 112 ) and EWL% ( 113 ) was found in others.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, in some studies, the effect of consuming prebiotics, probiotics, and synbiotics was not reported separately, and their collective impact was stated in comparison with the control group. BMI ( 56 , 110 ) and weight reduction ( 56 , 111 ) were observed in some studies, but a neutral effect on BMI ( 112 ) and EWL% ( 113 ) was found in others.…”
Section: Resultsmentioning
confidence: 98%
“…In accordance with the previous study, other investigators have found no relation between the use of perioperative probiotics/symbiotics and the attenuation of postoperative inflammatory markers [ 69 , 70 , 71 , 73 , 89 , 90 ]. Furthermore, in a meta-analysis that included studies with obese patients who were scheduled to have bariatric surgery, it was found that the perioperative use of pro-/pre-/symbiotics did not have a statistically significant effect on postoperative levels of CRP, IL-6, and TNF-α [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…The estimated market size for microecologics was about USD 850 billion in 2023, with a significant compound annual growth rate trend. Furthermore, broader research has shown that the effects of microecologics are not limited to chronic intestinal or systematic metabolic diseases but have also garnered increasing attention in recent years for their promising effects on enhancing sports performance in the athletic population [1][2][3][4]. However, there is a scarcity of reviews focusing on the effects and signaling pathways of Nutrients 2024, 16, 1602 2 of 19 microecologics specifically within this population.…”
Section: Introductionmentioning
confidence: 99%